Reviews of books and journals - Mora-García, José Pascual; Torres Aguilar, Morelos; Ramirez Trillos, Osmir; Abad, Alfredo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
In this section you will find reviews of books and journals related to the history of the Latin American education